1985
DOI: 10.2307/2061586
|View full text |Cite
|
Sign up to set email alerts
|

Entry into marriage and parenthood by young men and women: The influence of family background

Abstract: We investigate the influence of family background on early entry into marriage and parenthood among white, Hispanic, and black men and women ages 14 to 22 in the first (1979) wave of the National Longitudinal Survey of Youth. Family background is highly associated with early entry into marriage for whites of both genders and female Hispanics and also with early entry into parenthood for all groups except black males. Large group differences in family characteristics explain most of the difference between white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
118
1
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(132 citation statements)
references
References 25 publications
9
118
1
4
Order By: Relevance
“…Marriage is often a reason to migrate (Kofman 2004;Lievens 1999), especially if family visas are granted to spouses, and marriage and migration occur simultaneously when selection of migrants is based on family reunification policy (Tribalat 1996). The socialization hypothesis considers that exposure to certain norms and values during an immigrant's childhood (i.e., those of their country of origin) have long-lasting effects and are dominant in shaping individual behaviors (Michaël and Tuma 1985). In particular, socially recognized norms exist for the timing and sequencing of events associated with the transition to adulthood, and thus influence partnership dynamics (East 1998).…”
Section: Partnership Formation Among Immigrantsmentioning
confidence: 99%
“…Marriage is often a reason to migrate (Kofman 2004;Lievens 1999), especially if family visas are granted to spouses, and marriage and migration occur simultaneously when selection of migrants is based on family reunification policy (Tribalat 1996). The socialization hypothesis considers that exposure to certain norms and values during an immigrant's childhood (i.e., those of their country of origin) have long-lasting effects and are dominant in shaping individual behaviors (Michaël and Tuma 1985). In particular, socially recognized norms exist for the timing and sequencing of events associated with the transition to adulthood, and thus influence partnership dynamics (East 1998).…”
Section: Partnership Formation Among Immigrantsmentioning
confidence: 99%
“…There is a long tradition of research on the association between family of origin and fertility (Axinn, Clarkberg, and Thornton 1994;Barber 2000;Huinink 1987;Kolk 2014aKolk , 2014bMichael and Tuma 1985;Murphy 2013;Murphy and Wang 2001;Régnier-Loilier 2006;Rijken and Liefbroer 2009;Steenhof and Liefbroer 2008;Thornton 1980;Westoff and Potvin 1967). These studies found a positive relationship between the number of siblings and completed and, more seldom, expected family size.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with siblings have earlier births (Barber 2000(Barber , 2001Huinink 1987;Kolk 2014b;Michael and Tuma 1985;Rijken and Liefbroer 2009;Rindfuss and John 1983;Steenhof and Liefbroer 2008) and end up with more children (Murphy and Knudsen 2002;Murphy and Wang 2001). There are comparatively few, and mostly older, studies that have explored the association between the number of siblings and fertility desires or expectations.…”
mentioning
confidence: 99%
“…Una de las mas importantes razones que las hijas de madres adolescentes llegan a ser madres adolescentes es porque crecen en familias grandes con muchos hermanos (10,11,(15)(16)(17).…”
Section: Introductionunclassified
“…La forma como las madres sean capaces de controlar los comportamientos relacionados con el pololeo y la actividad sexual de sus hijas, influye en cuan rápidamente ellas llegan a ser madres. Las madres jóvenes y particularmente las madres solteras son menos capaces de controlar los comportamientos de la adolescente por lo tanto las hijas están en mas riesgo de comprometerse en comportamientos sexuales de riesgo y experimentar la maternidad adolescente (15)(16)(17). La separación de los padres es otro indicador de que las madres no sean capaces de supervisar adecuadamente el comportamiento sexual de las hijas (18,(19)(20)(21).…”
Section: Introductionunclassified